2022
DOI: 10.1038/s41398-022-02162-y
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated functional brain aging in major depressive disorder: evidence from a large scale fMRI analysis of Chinese participants

Abstract: Major depressive disorder (MDD) is one of the most common mental health conditions that has been intensively investigated for its association with brain atrophy and mortality. Recent studies suggest that the deviation between the predicted and the chronological age can be a marker of accelerated brain aging to characterize MDD. However, current conclusions are usually drawn based on structural MRI information collected from Caucasian participants. The universality of this biomarker needs to be further validate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 89 publications
0
3
1
Order By: Relevance
“…However, 98% of the participants are of Caucasian descent and they have relatively highly educated. Our cross-sectional study, despite an agreement with numerous cross-sectional brains aging studies ( 47 60 ) cannot make a definitive conclusion about accelerated aging and longitudinal studies are rather needed. In addition, more men, compared to women [58.1% (86/148) vs 51.2% 52/121)] reported alcohol drinking.…”
Section: Limitations and Conclusioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, 98% of the participants are of Caucasian descent and they have relatively highly educated. Our cross-sectional study, despite an agreement with numerous cross-sectional brains aging studies ( 47 60 ) cannot make a definitive conclusion about accelerated aging and longitudinal studies are rather needed. In addition, more men, compared to women [58.1% (86/148) vs 51.2% 52/121)] reported alcohol drinking.…”
Section: Limitations and Conclusioncontrasting
confidence: 60%
“…Premature, advanced, or accelerated brain aging are terms used to describe the gap between chronological age and estimated brain age derived from different machine learning algorithms. Accelerated brain aging is a non-specific observation that has been reported in many conditions such as major depression ( 47 50 ), psychosis ( 51 , 52 ), obsessive compulsive disorder ( 53 ), traumatic brain injury ( 54 , 55 ), tobacco smoking ( 56 ), diabetes mellitus ( 57 , 58 ), glioma patients following radiotherapy ( 59 ), and in healthy individuals with inadequate sleep ( 60 ). Few studies have reported negative association between accelerated brain aging and cognitive performance in patients with major psychoses ( 51 ), in older patients with depressive symptoms ( 61 ) and in patients with traumatic brain injury ( 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 It is a coordinated multisite project from China containing over 1000 MDD patients and normal controls and has been widely used by many studies. 8,19,20 In addition, we investigated the ability of altered spatiotemporal dynamics to assess MDD symptom severity.…”
mentioning
confidence: 99%
“…We further tested the main results in a large MDD rs‐fMRI database, that is, REST‐meta‐MDD (http://rfmri.org/REST-meta-MDD). 18 It is a coordinated multisite project from China containing over 1000 MDD patients and normal controls and has been widely used by many studies 8,19,20 . In addition, we investigated the ability of altered spatiotemporal dynamics to assess MDD symptom severity.…”
mentioning
confidence: 99%